Acute and chronic effect of stretching exercise on posture and flexibility of nurses and licensed practical nurses - Filho, José Nunes da Silva; Gurgel, Jonas Lírio; Silva, Elirez Bezerra da; Porto, Flávia (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: nurses and licensed practical nurses are among the most affected by postural deviations and their drawbacks, in the world. One of the ways to mitigate these ills is physical exercise, and it can be done at work environment, however, not as a form of workout gymnastics. Objective: To verify the effects of a muscle stretching exercise program (MSE) on posture and flexibility of nurses. Methods: Controlled clinical experiment with 28 nurses, aged 18-60 years, divided into experimental group (n=15) and control group (n=13). Anthropometric measures, flexibility and body posture of the trunk were performed. The intervention was of 08 weeks of MSE; each session lasted 40 min. The exercises had four sets of 30s of tension for 30s of the interval. An independent t-test compared the characteristics of the samples. The chi-square test treated the results regarding body posture, and the level of significance was p ≤ 0.05. Results: MSE promoted positive and chronic positive changes in the Experimental Group with attenuation of the concavities of the vertebral column in the cervical and thoracic regions. In the alignment of the cervical region and the curvature of the lumbar region, the effects were observed after the eight weeks of training, including sharp reduction of gibbosity in the scapula region after the exercise session. Conclusion: MSE promoted acute and chronic positive changes in body posture and flexibility in nurses.